Limitations of translation activation in masked priming: behavioural evidence from Chinese-English bilinguals and computational modelling - Wen, Yun; van Heuven, Walter J.B. (Elsevier, 2018)
Electrophysiological and behavioural evidence suggests that Chinese translations of English words are automatically activated when Chinese-English bilinguals read English words (e.g., Thierry & Wu, 2007; Wu & Thierry, 2010; Zhang, van Heuven, & Conklin, 2011). The present study investigated the impact of translation activation in three behavioural experiments with in total 118 Chinese-English bilinguals. First, we investigated whether Chinese phonology was the source of the effects of Chinese character repetition in the Chinese translations of English masked primes and targets (hidden repetition priming) observed in Zhang et al.’s (2011), and whether these hidden repetition priming effects were affected by Chinese morpheme complexity and prime duration. However, we failed to find any evidence of hidden repetition priming. An exact replication of Zhang et al. (2011) was conducted next, which again provided no evidence for hidden repetition priming. However, cross-language priming data collected with the same group of participants did reveal masked translation priming and crucially Chinese character repetition priming with masked Chinese primes and English targets (partially hidden repetition priming), indicating that the activation of Chinese translations in the masked priming paradigm is limited to English target words. Computational modeling work provided further support that translation form activation is limited to target words in the masked priming paradigm.